Mendelian randomisation implicates hyperlipidaemia as a risk factor for colorectal cancer. Issue 12 (6th April 2017) - Rodriguez‐Broadbent, Henry; Law, Philip J.; Sud, Amit; Palin, Kimmo; Tuupanen, Sari; Gylfe, Alexandra; Hänninen, Ulrika A.; Cajuso, Tatiana; Tanskanen, Tomas; Kondelin, Johanna; Kaasinen, Eevi; Sarin, Antti‐Pekka; et al.
Abstract : While elevated blood cholesterol has been associated with an increased risk of colorectal cancer (CRC) in observational studies, causality is uncertain. Here we apply a Mendelian randomisation (MR) analysis to examine the potential causal relationship between lipid traits and CRC risk. We used single nucleotide polymorphisms (SNPs) associated with blood levels of total cholesterol (TC), triglyceride (TG), low‐density lipoprotein (LDL), and high‐density lipoprotein (HDL) as instrumental variables (IV). We calculated MR estimates for each risk factor with CRC using SNP‐CRC associations from 9, 254 cases and 18, 386 controls. Genetically predicted higher TC was associated with an elevated risk of CRC (odds ratios (OR) per unit SD increase = 1.46, 95% confidence interval [CI]: 1.20–1.79, p = 1.68 × 10 −4 ). The pooled ORs for LDL, HDL, and TG were 1.05 (95% CI: 0.92–1.18, p = 0.49), 0.94 (95% CI: 0.84–1.05, p = 0.27), and 0.98 (95% CI: 0.85–1.12, p = 0.75) respectively. A genetic risk score for 3‐hydoxy‐3‐methylglutaryl‐coenzyme A reductase ( HMGCR ) to mimic the effects of statin therapy was associated with a reduced CRC risk (OR = 0.69, 95% CI: 0.49–0.99, p = 0.046). This study supports a causal relationship between higher levels of TC with CRC risk, and a further rationale for implementing public health strategies to reduce the prevalence of hyperlipidaemia. Abstract : What's new? While observational studies have suggested an association between blood cholesterol levels and colorectal cancer (CRC), they do not establish causality and may be influenced by confounding factors. Here the authors used Mendelian randomization, the relationship between genetic risk scores for lipid traits and CRC, to provide new evidence for a causal link between both. Their results point to hyperlipidaemia as an important target for CRC prevention in the population.